Mudanças no uso da terra decorrentes da expansão da cultura da cana-de-açúcar na região oeste do estado de São Paulo - Lourenzani, Wagner Luiz [UNESP]; Caldas, Marcellus Marques (Universidade Federal de Santa Maria, 2014)
The demand for energy alternatives to oil are increasing global biofuel production and, consequently, the biofuel crops cultivation. In Brazil, the emergence of flex-fuel vehicles resumed the importance of ethanol production, resulting in a new phase of Brazilian sugar cane crop expansion. Several issues related to the sustainability of biofuel production have been discussed in the literature, such as the effect on food production and food security, the environmental impact of land use change and social effects in the field. This study aims to analyze the land use change in the Oeste Paulista region, caused by the expansion of sugar cane cultivation. Between 2003 and 2012, the Oeste Paulista region represented more than half of the expansion of this crop in São Paulo state, the largest producer in Brazil. This paper used the Shift-Share model to decompose the agricultural areas variation and to calculate the replacement of the main activities analyzed. The results revealed that, in the analyzed region, the expansion of sugar cane area has occurred predominantly by replacing pasture and, consequently, by cattle activity

A demanda por alternativas energéticas tem aumentando a produção mundial de biocombustíveis e, consequentemente, o cultivo das culturas agrícolas. No Brasil, o lançamento dos veículos bicombustíveis propiciou a retomada da importância da produção de etanol e, consequentemente, numa nova fase de expansão do cultivo de cana-de-açúcar. Diversas questões relacionadas à sustentabilidade da produção de biocombustíveis têm sido discutidas na literatura, tais como o efeito na produção de alimentos e na segurança alimentar, o impacto ambiental da mudança do uso da terra e os efeitos sociais no campo. Este trabalho pretende analisar as mudanças no uso da terra na região Oeste Paulista, provocadas pela expansão do cultivo da cana-de-açúcar. Na última década (2003 a 2012), a região Oeste Paulista representou mais da metade da expansão dessa cultura no estado de São Paulo, maior estado produtor brasileiro. O método utilizado foi o Modelo Shift-Share, que, por meio da decomposição da variação das áreas, possibilitou calcular os efeitos escala e substituição das principais atividades em análise. Este trabalho revela que a expansão da cultura da cana-de-açúcar na região estudada ocorreu predominantemente pela substituição de áreas de pastagem e, consequentemente, da atividade pecuária
Land use change from the sugar cane expansion in the western region of São Paulo state, Brazil
Keywords: cana-de-açúcar; expansão; mudança do uso da terra; sugar cane; expansion; land use change